2020
DOI: 10.3390/diagnostics10040238
|View full text |Cite
|
Sign up to set email alerts
|

Grip Strength: A Useful Marker for Composite Hepatic Events in Patients with Chronic Liver Diseases

Abstract: Here we sought to clarify the prognostic impact of sarcopenia-related markers (grip strength (GS), muscle mass using bioimpedance analysis and patient quality of life as assessed by the 36-Item Short-Form Health Survey (SF36)) in patients with chronic liver diseases (CLDs, n = 411; 160 liver cirrhosis patients; median age, 64 years) on the incidence of composite hepatic events (CHEs). A GS decrease was defined as <26 kg in men and <18 kg in women, while a skeletal muscle mass index (SMI) decrease was def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
16
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 56 publications
1
16
2
Order By: Relevance
“…Since HCC often recurs and requires repeated treatments, the loss of muscle strength may have been a stronger factor than the loss of skeletal muscle mass in the process. Indeed, recently published studies have reported that GS (muscle strength) has a greater effect on the prognosis than the skeletal muscle mass in community-dwelling elderly people, as well as patients with chronic liver disease [ 19 , 20 , 21 ]. In fact, the European Working Group on Sarcopenia in Older People (EWGSOP) guidelines state that low muscle strength is the primary parameter of sarcopenia, because muscle strength is the most reliable measure of the muscle function [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since HCC often recurs and requires repeated treatments, the loss of muscle strength may have been a stronger factor than the loss of skeletal muscle mass in the process. Indeed, recently published studies have reported that GS (muscle strength) has a greater effect on the prognosis than the skeletal muscle mass in community-dwelling elderly people, as well as patients with chronic liver disease [ 19 , 20 , 21 ]. In fact, the European Working Group on Sarcopenia in Older People (EWGSOP) guidelines state that low muscle strength is the primary parameter of sarcopenia, because muscle strength is the most reliable measure of the muscle function [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…These studies included a variety of tumors, including lung, colorectal, breast and prostate cancers, suggesting that the effect of GS may not be independent of the cancer type. Furthermore, it has already been shown that GS has a stronger prognostic impact than SMI in CLD, the underlying disease of HCC [ 19 , 21 ]. These results suggest that a low GS is a poor prognostic factor for systemic chemotherapy other than lenvatinib in u-HCC.…”
Section: Discussionmentioning
confidence: 99%
“…However, those studies had individually defined cut‐off values for a low SMI and were not guideline‐based. More recent studies have reported that low grip strength (muscle strength) has a greater effect on the prognosis than a low skeletal muscle mass in patients with CLD as well as patients with HCC treated with lenvatinib 45–47 . In fact, the European Working Group on Sarcopenia in Older People (EWGSOP) guidelines state that a low muscle strength is the primary parameter of sarcopenia, as muscle strength is the most reliable measure of the muscle function 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, recently published studies have reported that GS (muscle strength) has a greater effect on the prognosis than the skeletal muscle mass in community-dwelling elderly people, as well as patients with chronic liver disease [17][18][19] hospital stays, increased functional limitations, poor health-related quality of life and death). In addition, the measurement of GS is usually easier than the measurement of skeletal muscle mass because the measurement of skeletal muscle mass requires special equipment, such as a bioelectrical impedance analysis (BIA), dual-energy X-ray absorptiometry (DEXA) and CT.…”
Section: Discussionmentioning
confidence: 99%